Gasification of sawdust and wood chips in a fixed bed under autothermal and stable conditions (2014)
The high potential in Colombian agroforestry residues can be exploited through gasification; however, biomass pretreatment must be minimized to increase process efficiency. In this article, the gasification of woodchips and sawdust mixtures (0, 30, 70, and 100% of sawdust, wt%) with three air velocities below the fluidization one is studied. Experiments were carried out on a lab scale fixed-bed reactor. For sawdust percentages greater than 30%, the particle size distribution causes the fluidized smaller particles to leave from the reactor. Biomass losses are due to the weight and size reduction of the particles during drying and devolatilization subprocesses; this instability can lead to formation of bridging and extinction of the reaction front. © Copyright Taylor & Francis.